(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Irritable bowel syndrome (IBS) is a common and bothersome disorder in children with an increasing prevalence noted during the past two decades. It has a significant effect on the lives of affected children and their parents and poses a significant burden on healthcare systems. As the patho-physiology of IBS is multifactorial It is difficult to overcome the therapeutic demand of childhood IBS using the same conventional therapeutic agents. The treatment trials are still going on to understand the paediatric IBS and currently focusing on multiple combined interventions in modern science. Background: A 14 years old male patient came to OPD (29/02/2020) having complaint of frequent abdominal pain with increased frequency of motion along with visible mucus discharge whole day since 15 days with frequent episodes since last 2 years. Methodology: In Ayurveda this problem comes under Jatharagni dusti and the present case has been successfully treated as per treatment regimen of Grahani chikitsa. Result: The complete relief has been seen in 6 weeks.